A content analysis of an online pro-eating disorder community on Reddit. (March 2018) - Sowles, Shaina J.; McLeary, Monique; Optican, Allison; Cahn, Elizabeth; Krauss, Melissa J.; Fitzsimmons-Craft, Ellen E.; Wilfley, Denise E.; Cavazos-Rehg, Patricia A.
Highlights: Eating and shape concerns were the most prevalent themes in the analyzed comments. Comments often disclosed guilt about eating, eating in secret, and feeling fat. Praising individuals who maintain their eating disordered behaviors was common. Abstract: Pro-eating disorder communities provide a refuge for individuals with eating disorders (EDs) who are ambivalent about seeking treatment. We investigated a pro-ED community on Reddit, an anonymous social networking platform with topical forums, to identify expression of behaviors aligned with ED symptoms and support for these behaviors. A content analysis on four weeks of topic-specific discussion threads ( N  = 125 comments, 115 replies to comments) was conducted to identify behaviors consistent with ED psychopathology and support for these behaviors (informational, tangible assistance, esteem/emotional support). Results indicated that the content aligned with expressions of clinically relevant ED psychopathology, with eating concerns (49/125) and shape concerns (47/125) being most prevalent. The majority (92/115) of replies provided esteem/emotional support to the comment author. Online interventions and/or recovery programs are needed to counteract reinforcing dialogue that occurs on social media sites, like Reddit, and promote ED recovery through supportive messages on these platforms.